Analisis Tingkat Kerentanan Bencana Banjir di Kab.Bandung Dengan Menggunakan Sistem Informasi Geografi - Rina Panggabean; Alam Mustaqim Nst; Sri Sulastri Sitohang; Beta Ria Sihaloho; Romaulina Br. Sihotang; Riki Rahmad; Elsa Kaldiana (Geosfera: Jurnal Penelitian Geografi, 2025)
Flood disasters are one of the hydrometeorological hazards that frequently occur in Bandung Regency and have significant impacts on the environment, as well as the social and economic conditions of the community. This study aims to analyze the level of flood vulnerability in Bandung Regency by utilizing Geographic Information Systems (GIS). The research employs a descriptive–quantitative approach by integrating several vulnerability parameters, including population density, land use, distance of settlements to rivers, slope, rainfall, and drainage infrastructure conditions. Each parameter is weighted through a scoring technique and overlaid using GIS software to produce a flood vulnerability zoning map.The analysis shows that Bandung Regency exhibits considerable variations in vulnerability levels, ranging from low, medium, to high categories. Areas with high vulnerability are generally located in lowland zones, near major river channels, have high population density, and are dominated by residential land use and urban activities. Meanwhile, areas with low vulnerability are situated in hilly regions with steeper slopes and relatively good vegetation cover. The resulting vulnerability map can be used as a basis for spatial planning, disaster mitigation, and decision-making by local authorities.This study emphasizes the importance of utilizing GIS in spatial analysis of flood vulnerability, as it provides accurate geographic visualization and information to support effective and sustainable disaster risk reduction efforts.